Strategic focus in military conflict confrontation in Ukraine - Lepskyi, Maksym (Skhid, 2015)
The article examines the strategy and strategizing as a result of the process of strategy formation of internal and external conflicts in Ukraine. The author explores the essential characteristics of the strategy and pays special attention to such an essential characteristics of the integrity of the subject, of Ukraine. The levels of strategic focus of the subject in the process of reconnaissance in the conflict and military situation in the country are viewed. The research is also aimed at the challenges and problems of the integrity of Ukraine, internal contradictions and gaps, challenges for the balance of power in the geopolitical confrontation, alternative actions for the weaker entity. The author provides research of the importance of the subject to focus on suchprocesses as differentiation and integration of war, its new types (e.g., hybrid and cross-system wars). The research focus is on the analysis of spatial, temporal and chronotopic definition of modern war. Particular attention is paid in the work to the focus on the subject of peace or war, life or death in the reconnaissance strategy to overcome the conflict or military confrontation.